Antenna Design Solutions for RFID Tags Based on Metamaterial-Inspired Resonators and Other Resonant Structures - Zuffanelli, Simone (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This book describes innovative design solutions for radio-frequency identification (RFID) tags and antennas. Focusing mainly on passive ultra-high-frequency (UHF)-RFID tag antennas, it examines novel approaches based on the use of metamaterial-inspired resonators and other resonant structures as radiating elements. It also offers an exhaustive analysis of the radiation properties of several metamaterial-inspired resonators such as the split ring resonator (SRR) and related structures. Further, it discusses in detail an innovative technology for the RFID tagging of optical discs, which has demonstrated a significant improvement over the state of the art and resulted in a patent. By covering the entire research cycle of theory, design/simulation and fabrication/evaluation of RFID tags and antennas, while also reporting on cutting-edge technologies, the book provides graduate students, researchers and practitioners alike with a comprehensive and timely overview of RFID systems, and a closer look at several radiating structures.